Ventriculoperitoneal shunt placement for POEMS syndrome. Issue 10 (October 2015) - Alvarez-Breckenridge, Christopher A.; Attiah, Mark A.; Zachariah, Marcus; Gummadavelli, Abhijeet; Yang, Jimmy; Codd, Patrick J.
Highlights The constellation of clinical symptoms that include polyneuropathy, organomegaly, endocrinopathy, monoclonal protein elevation, and skin changes comprises the diagnosis of POEMS syndrome. Papilledema and elevated intracranial pressure (ICP) have been associated with POEMS syndrome. Treatment of associated symptoms of elevated ICP, including headaches and diplopia, seen in POEMS syndrome, have typically involved acetazolamide and large volume lumbar puncture. This case report is the first documented placement of a venticuloperitoneal shunt for elevated ICP associated with POEMS syndrome.